Evaluacion de la composicion de los lodos generados en el proceso de potabilización en la planta ecológica de tratamiento de agua cruda y el impacto en la calidad de agua en la quebrada Quillotucto Soritor, 2015 - Chu Rios, Siomi (2017)
The main objective of the research work was to evaluate the composition of the Sludge generated in the process of purification in the ecological treatment plant of Raw water and the impact on the quality of the water of the Quillotucto Soritor, for which samples were taken from the sludge in the water treatment plant and the water Of the Quebrada Quillotucto before and after the muds were poured into these waters, The sampling was performed twice because the cleaning time of the plant Is about every three months at a time when the sludge is discharged into the water ravine. The parameters evaluated in the sludge were the total solids found An average of 124 294.5 mg / L, aluminum with an average of 20 636 mg / L, iron Average of 8 501.5 mg / L, average calcium of 334.6 mg / L, samples that were sent To the Regional Water Laboratory-Regional Government of Cajamarca, the parameter evaluated In situ was the (pH) that had on average 6.65; The same way for the water of the Broken Quillotucto the parameters were the same pre-dumping of the sludge, Obtaining an average pH of 5.78, total solids 304.5 mg / L, aluminum 6.92 mg / L, calcium 8.77 mg / L and iron 2.84 mg / L, post-dumping of the sludge average pH 6.7, solids Total 4 087.85 mg / L, aluminum 615.25 mg / L, calcium 32.89 mg / L and iron with 179.9 mg / L, The results obtained from the water sampling of the Quebrada Quillotucto allowed Compared with the Environmental Quality Standards (ECA), thus determining the Level of aluminum, total solids and iron post-dumping of the sludge, however the PH and calcium do not exceed these standards. In addition, to determine the contribution of The sludge in the contamination of the waters of the Quebrada Quillotucto was proceeded Through the unilateral left student t distribution with 95% confidence, with a Results of -3.03; Able to test the negative impacts generated by sludge in the Quality of the water of the Quillotucto ravine.